What Drives Outpatient Care Costs in Kenya? An Analysis With Generalized Estimating Equations - Mwenda, Ngugi; Nduati, Ruth; Kosgei, Mathew; Kerich, Gregory (Frontiers in Public Health, 2021)
Objective: This study aimed to identify the factors associated with outpatient expenses incurred by households in Kenya. Background: The problem of outpatient healthcare expenses incurred by citizens in countries with limited resources has received little attention. Thus, this study aimed to determine the predictors of household spending on outpatient expenses in Kenya. Method: We conducted a cross-sectional analysis on households in Kenya using data from the 2018 Kenya Household Health Expenditure and Utilization Survey. We applied the generalized estimating equations method to determine the best subset of predictors of outpatient care cost. Findings: The best predictors of outpatient care expenses in Kenya are age, wealth index, and education level of the household head. Conclusions: There were no differences regarding age in the mean spending on outpatient care. Moreover, we found that the cost of outpatient care changes with age in a sinusoidal manner. We observed that rich households spent more on outpatient care, mostly owing to their financial ability. Households whose heads reported primary or secondary school education level spent less on outpatient costs than households headed by those who never went to school.